Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

( *) If tan theta 1 = k cot theta 2 then cos (theta1 – theta2) / cos (theta1 + theta 2) =

( *)
If tan theta 1 = k cot theta 2 then cos (theta1 – theta2) / cos (theta1 + theta 2) =

Grade:11

1 Answers

Nishant Vora IIT Patna
askIITians Faculty 2467 Points
7 years ago
Hello student, Please find the answer to your question below

tan Ø 1 = k cotØ 2
=> tan Ø 1 * tanØ 2 = k

Now cos (theta1 – theta2) / cos (theta1 + theta 2)
=[cos Ø1 cos Ø2 – sin Ø1 sin Ø2] / [cos Ø1 cos Ø2 + sin Ø1 sin Ø2]
Divide numerator and denomenator by cos Ø1 cos Ø2
So you will get [1 – tan Ø 1 * tanØ 2] / [1 + tan Ø 1 * tanØ 2] = (1 – k)/(1 + k)

Ans

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free